Comparison of digital volume tomography and high-resolution computed tomography in detecting superior semicircular canal dehiscence – a temporal bone study. (September 2015) - Bremke, Martin; Luers, Jan-Christoffer; Anagiotos, Andreas; Gostian, Antoniu-Oreste; Dorn, Franziska; Kabbasch, Christoph; Unkel, Claus; Höllering, Jens; Beutner, Dirk
Abstract Conclusion: In detecting a thin bony coverage of a superior semicircular canal (SSC), digital volume tomography (DVT) scans in Poeschl projection seem to be superior to high-resolution computed tomography (CT) scans. Still, a definite diagnosis of SSC dehiscence (SSCD) is not possible with any radiologic imaging technique. Objective: To compare CT and DVT to find out whether DVT is equal, better or worse in showing a thin bony layer on top of an SCC. Methods: In 11 human temporal bone specimens, the SSC was microscopically blue-lined leaving a thin bony coverage on top of it. All specimens were assessed with both high-resolution CT and DVT. After reconstructing the images in Stenvers and Poeschl projections, all images were evaluated by five independent examiners experienced in radiologic imaging of the temporal bone using a four-point ordinal scale, from 1 (distinct dehiscence) to 4 (distinct coverage). Results: The mean score for all CT scans was 2.58 compared with 3.22 for DVT scans (p = 0.000). Poeschl projection showed a mean score of 3.25 compared with 2.55 for Stenvers projection (p = 0.000). The best imaging modality was found to be DVT scans in Poeschl projections, with a mean score of 3.60.